Frederick Harbison, Joan Maruhnic y Jane Resnik. Quantitative analysis of modernization and development, industrial relations section. New Jersey : Princeton University, 1970. 335 p. - Hodara B., Joseph (El Colegio de México A.C., 1972)
FREDERICK HARBISON, JOAN MARUHNIC y JANE RESNIK, Quantitative Analysis of Modernization and Development, Industrial Relations Section, New Jersey, Princeton University, 1970.